Impact of Product Innovation on Compentency Level of Fast-Food Chain in Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of the study is to determine the impact of product innovation on the competencylevel of the fast-food chain in Quezon City in terms of age, gender, educational attainment,civil status, product innovation, process innovation, paradigm innovation, and positioninnovation.The result of the study reveals that most respondents are females between the ages of fewerthan 25 years old. The impact of product innovation on the competency level of fast-foodchains in terms of product innovation is that new varieties of products attract customers, andthe preference of the consumer and expectation in service and goods is "Agreed." The impactof product innovation on the competency level of the fast-food chain in terms of processinnovation. The new product that is highly recommended to other customers is a "Agree." Theimpact of product innovation on the competency level of the fast-food chains in terms ofparadigm innovation using delivery services makes it easier to purchase recently launchedgoods. The impact of product innovation on the competency level of the fast-food chains interms of position innovation and the variety of products helps to increase the company'sincome.The impact of product innovation on the competency level of the fast-food chains in terms ofposition innovation and the variety of products helps to increase the company's income. Theproblems encountered by respondents in product innovation at the competency level arefinancial capacity, marketing strategy, cost and budget management, customer service,pricing strategy, product consistency, health and hygiene, and employee training. Overall, theresearchers recommend improving dealing with consumer and employee complaints andconcerns; employees must have better training for quality service and fast and efficientservice that consumes the time of customers to increase the demand.
Keywords: Business